Art Summit Indonesia 1995. - Indonesia. Direktorat Jenderal Kebudayaan; Art Summit Indonesia 1995 Jakarta, Indonesia). (Jakarta Direktorat Jenderal Kebudayaan, Departemen Pendidikan dan Kebudayaan, Republik Indonesia, 1997)
International music and dance festival, Jakarta 1995.
In Indonesian.
Keywords: Dance festivals -- Indonesia -- Jakarta; Music festivals -- Indonesia -- Jakarta